Private sustainability governance in the making – A case study analysis of the fragmentation of sustainability governance for the gold sector - Heidingsfelder, Jens (Resources Policy, 2019)
Governance is needed to address sustainability challenges along global value chains. Yet, the multiplicity or fragmentation of public and private sustainability governance resembles a potential hurdle for coping with sustainability challenges. This fragmentation is also intriguing from a research perspective, as little is known about the drivers of governance fragmentation in specific commodity sectors. This study assesses the fragmentation of sustainability governance in the global gold sector. Four general factors for fragmentation are derived from the literature: contextual factors, intra- and inter-organizational factors as well as scope of governance. A comprehensive case study, including a qualitative analysis of 26 in-depth interviews with experts in the gold sector, is used to investigate these general factors in the case of gold and to derive gold-specific factors for fragmentation. The five key findings are that, first, specific industry characteristics of the gold sector create actor-specific governance needs that lead to a multiplicity of governance schemes. Second, key governance references exist in the case of gold, but leave room for interpretation, thus encouraging a multiplicity of governance. Third, intra-organizational factors considerably impact the fragmentation of governance for gold, regarding different governance initiators and members, organizational logics, missions and ‘business models’ and the framing of sustainability. Fourth, the scope of governance strongly explains fragmentation in the gold sector. Fifth, competition between governance makers for gold provides only weak explanations for the resulting fragmentation. A conceptual framework is introduced that encapsulates general factors of fragmentation from the literature and gold-specific factors from the empirical findings. It serves to refine, enrich and display factors of fragmentation in their interaction in the gold sector. Insights from this study expand the scholarly knowledge on fragmented sustainability governance and provide a starting point for further cross-case and comparative studies of fragmented sustainability governance.
CRIS-Team Scopus Importer:2019-09-03
Keywords: case study; fragmentation; gold sector; Private governance; sustainability; sustainability scheme; Nachhaltigkeit